Purification and Some Chemical Properties of Thrombin-Like Enzyme from Trimeresurus Flavoviridis Venom - Kosugi, T; Ariga, Y; Nakamura, M; Kinjo, K (Thrombosis and Haemostasis, 1986)
There has been no previous report indicating whether thrombin-like enzyme is contained in the venomof Trimeresurus flavoviridis whichhas the strongest toxic effect in the case of Habu bite. The presentstudy was undertaken to clarify the existence of thrombin-like enzyme in Trimeresurus flavoviridis venom. As a starting material, lyophilized crude venom of Trimeresurus flavoviridis was used, and ammonium sulphate fractionation, gel filtration using Sephadex G-25, Sephadex G-150 and arginine-Sepharose affinity chromatography were carried out to separate and purify a thrombin-like enzyme from the crude venom. The enzyme was purified to a 137-fold increase in specific activity and the purified preparation revealed a single band on SDS-PAGE. The molecular weight of the enzyme was estimated to be 65,000-70,000 daltons by means of SDS-PAGE and gel filtration, and its isoelectric point was pH 4.5-5.5. Furthermore, the optimal pH of the enzyme was in the range of pH 8.0 to 8.5. Some of the differences in enzymatic properties between this enzyme and bovine thrombin were studied. The snake enzyme could coagulate only rabbit plasma and convert only purified rabbit fibrinogen to fibrin gel. In addition, this thrombin-like enzyme released only fibrinopeptide A from purified rabbit fibrinogen and did not release fibrinopeptide B.
Keywords: Thrombin-like enzyme; Fibrinopeptide A; Snake venom(T. flavoviridis)